STRATEGI PENANAMAN NILAI-NILAI EKONOMI KREATIF PADA SANTRI PONDOK PESANTREN AL-ISTIQOMAH DESA SAMA GUNA LOMBOK UTARA - Muhammad Yakub Ismail; Habibul Umam Taqiuddin (Universitas Islam Negeri Mataram, 2021)
The cultivation of these creative economic values can be transformed to anyone, it can be in the community, including in Islamic boarding schools. Along with the times and technological advances that are increasingly advanced, Islamic boarding schools must innovate by providing business mentality or entrepreneurship. Providing entrepreneurial provisions trains students to be entrepreneurs in actualizing their abilities as entrepreneurs or entrepreneurship. This research is a qualitative research with a descriptive approach that aims to describe the strategy carried out by the Al-Istiqomah Islamic Boarding School Kapu, Sama Guna Village, Tanjong District, North Lombok Regency in the transformation of creative values in students. The subjects of this study were the managers of the al-Istiqomah Islamic Boarding School and the informants of 4 students, ustadz and ustadzah. The data collection method used consisted of interviews, documents, and observation. The data analysis method used is by means of data reduction, data presentation, and drawing conclusions.